Robust trajectory-tracking for a Bi-copter Drone using IBKS and SPNN Adaptive Controller - Abedini, Arian; Bataleblu, Ali Asghar; Roshanian, Jafar (Digest book (International Conference on Robotics and Mechatronics. Online), 2022)
The robustness and low dependence on an accurate aerodynamics model of control strategies based on incremental dynamics (ID) are getting prominence among aerial robot researchers. This study integrates incremental control action with the backstepping design methodology to yield results that support a robust nonlinear flight control strategy for a bi-copter drone. The proposed method, in comparison with traditional backstepping, incrementally stabilizes or tracks the nonlinear system's control variables while compensating for undesirable factors such as external disturbances. This approach implies, in a sense, a trade-off between the accuracy of the dynamic model and actuators data. As a result, the dependency of the modeled bi-copter system is significantly reduced, overcoming the major robustness flaw of traditional model-based flight control strategies. Finally, simulation results validate the proposed controller's tracking ability and superior robustness under external disturbance when compared to traditional backstepping methodologies for a circle-shaped path.